2006
DOI: 10.1126/science.1128314
|View full text |Cite
|
Sign up to set email alerts
|

Surface Crystallization in a Liquid AuSi Alloy

Abstract: X-ray measurements reveal a crystalline monolayer at the surface of the eutectic liquid Au 82 Si 18 , at temperatures above the alloy's melting point. Surfaceinduced atomic layering, the hallmark of liquid metals, is also found below the crystalline monolayer. The layering depth, however, is threefold greater than that of all liquid metals studied to date. The crystallinity of the surface monolayer is notable, considering that AuSi does not form stable bulk crystalline phases at any concentration and temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
182
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(206 citation statements)
references
References 27 publications
24
182
0
Order By: Relevance
“…For instance, it is known that several materials, such as normal alkanes (11), alcohols (12), and certain alloys (13), can undergo surface freezing. However, it is not yet known with predictive certainty what makes a material susceptible to surface-induced crystallization.…”
mentioning
confidence: 99%
“…For instance, it is known that several materials, such as normal alkanes (11), alcohols (12), and certain alloys (13), can undergo surface freezing. However, it is not yet known with predictive certainty what makes a material susceptible to surface-induced crystallization.…”
mentioning
confidence: 99%
“…Si) and crystal structures. [2][3][4][5][6] More recently, a stable two-dimensional (2D) gold silicide has been evidenced following surface crystallisation of the eutectic Au 82 Si 18 liquid above the eutectic temperature T E ÂŒ 359 C. 7 It was shown to have an Au 4 Si 8 composition and a rectangular crystal structure, stable up to 371 C. 8 This 2D crystalline silicide phase has also been obtained under ultra high vacuum (UHV) conditions following deposition of a 3 nm Au layer on a Si(100) substrate and subsequent annealing above the eutectic temperature (T E ). 9 Other Au/Si alloys were also obtained in UHV conditions either at room temperature (RT) [10][11][12] or by annealing thicker Au films (10-100 nm) deposited on a Si substrate.…”
mentioning
confidence: 99%
“…2,3 Recent experimental studies have shown marked differences between the two systems, however. Whereas eutectic Au-Si exhibits a liquid surface structure with strong Si surface enrichment and planar ordering, 4 this is not observed in eutectic Au-Ge. 5 The coordinations in the eutectics also show differences.…”
mentioning
confidence: 93%
“…5 The coordinations in the eutectics also show differences. 6 Recently, it was predicted that a compound Au 4 Si could exist in Au-Si ͑Ref. 7͒ in spite of it being known as a noncompound-forming system.…”
mentioning
confidence: 99%